2009
DOI: 10.1124/mol.109.057430
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Inhibits Superoxide Dismutase 1 Gene Transcription in Human Cancer Cells: The Involvement of Peroxisome Proliferator-Activated Receptor α and Hypoxia-Inducible Factor-2α Signaling

Abstract: Docosahexaenoic acid (DHA; 22:6) is known to have anticancer activity, but its mechanisms of action remain to be further elucidated. We recently demonstrated that DHA downregulates superoxide dismutase (SOD) 1 gene expression, thereby weakening cellular antioxidant forces and enhancing cytotoxicity in various human cancer cells. The objective of this study was to investigate the mechanism of the inhibitory effect of DHA on SOD-1 gene expression in human cancer cells. A reporter gene assay indicated that DHA su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Western Blot Analysis-Western blot was performed as we described previously (24). In brief, cells were lysed with the lysis buffer, sonicated on ice, and centrifuged at 15,000 ϫ g for 15 min to remove insoluble material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western Blot Analysis-Western blot was performed as we described previously (24). In brief, cells were lysed with the lysis buffer, sonicated on ice, and centrifuged at 15,000 ϫ g for 15 min to remove insoluble material.…”
Section: Methodsmentioning
confidence: 99%
“…Co-immunoprecipitation-Co-immunoprecipitation using Ago2 antibody was performed as described previously (24). In short, cells growing in 100-mm dishes were washed with PBS and harvested by adding 150 l of IP buffer (10 mM Tris-HCl, pH 7.4, 50 mM NaCl, 0.5 mM EDTA, 1 mM PMSF, and 1% Triton X-100).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies demonstrated that these two drugs have anticancer properties in various model systems (9 -11), but the mechanisms behind their actions remain to be elucidated. We have reported previously that activation of PPAR␣ mediates the anticancer action of docosahexaenoic acid, likely through down-regulation of hypoxia signaling (12,13). We therefore hypothesized that the anticancer properties of PPAR␣ agonists may similarly be due to suppression of HIF-1␣ signaling in human cancer cells.…”
Section: Activation Of Peroxisome Proliferator-activated Receptor ␣ (mentioning
confidence: 97%
“…Co-immunoprecipitation experiments were performed using an anti-Argonaute 2 (Ago2) antibody (Wako Pure Chemical Industries, Tokyo, Japan), as described previously. (12) The RNA was isolated from precipitates using ISOGEN reagent (Nippon Gene, Osaka, Japan) according to the manufacturer's instructions. Reverse transcriptase reactions were performed using M-MLV reverse transcriptase (Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%